First record of the genus Spathiomorpha Tobias, 1976 (Hymenoptera: Braconidae: Doryctinae) in the New World, with the description of a new species - Belokobylskij, Sergey A.; Zaldívar-Riverón, Alejandro (Zootaxa, 2022)
A new species of the doryctine genus Spathiomorpha Tobias, 1976, S. mexicana sp. nov., is described and illustrated from montane region in the state of Chiapas, southeast Mexico. This represents the first record of this genus in the New World. A key to the currently described species of Spathiomorpha genus is provided.